2017
DOI: 10.1017/s0950268817002667
|View full text |Cite
|
Sign up to set email alerts
|

A severe gastroenteritis outbreak ofSalmonella entericaserovar Enteritidis PT8, with PFGE profile XbaI.0024 and MLVA profile 2-9-7-3-2 following a christening reception, Greece, 2016

Abstract: In June 2016, a Salmonella enterica serovar Enteritidis outbreak (n = 56) occurred after a christening reception in Central Greece, mainly affecting previously healthy adults; one related death caused media attention. Patients suffered from profuse diarrhoea, fever and frequent vomiting episodes requiring prolonged hospitalisation and sick leave from work, with a 54% hospital admission rate. The majority of cases experienced serious illness within <12 h of attending the party. We investigated the outbreak to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A survey about the worldwide distribution in human cases (Ekdahl et al 2005), suggested S. Enteritidis is the most prevalent serovar in all but Africa, India and America. Besides, there have happened a series of outbreaks triggered by S. Enteritidis (Mandilara et al 2017;Pavlova et al 2018;Wright et al 2015). Since researchers realized this serotype posed great risks to food industry and public health, a great many relevant reports have been published to gure out the mechanisms of the virulence.…”
Section: Introductionmentioning
confidence: 99%
“…A survey about the worldwide distribution in human cases (Ekdahl et al 2005), suggested S. Enteritidis is the most prevalent serovar in all but Africa, India and America. Besides, there have happened a series of outbreaks triggered by S. Enteritidis (Mandilara et al 2017;Pavlova et al 2018;Wright et al 2015). Since researchers realized this serotype posed great risks to food industry and public health, a great many relevant reports have been published to gure out the mechanisms of the virulence.…”
Section: Introductionmentioning
confidence: 99%
“…Typhimurium), and causes food poisoning in human [3]. They have been reported for causing more than ~140 foodborne illness throughout the world [4][5][6][7][8]. As per the Centers for Disease Control and Prevention (CDC), typhoid fever causes ~22 million new cases and ~200,000 deaths every year across the world [9,10].…”
Section: Introductionmentioning
confidence: 99%